Предмет: Алгебра,
автор: Аноним
упростите выражение:
Приложения:
Ответы
Автор ответа:
0
1) в скобках
(x*x -(x -y)(x+y)) /x(x+y) =(x² -(x² -y²)) /x(x+y) = -y² /x(x+y)
2) при делении дробь переворачиваем и будет умножение
y/(x+y) *x(x+y)/(-y²) =(y*x(x+y)) /(-y²)(x+y) = -x/y
ответ: -x/y
(x*x -(x -y)(x+y)) /x(x+y) =(x² -(x² -y²)) /x(x+y) = -y² /x(x+y)
2) при делении дробь переворачиваем и будет умножение
y/(x+y) *x(x+y)/(-y²) =(y*x(x+y)) /(-y²)(x+y) = -x/y
ответ: -x/y
Похожие вопросы
Предмет: История,
автор: violettasumy201
Предмет: Окружающий мир,
автор: Rizich
Предмет: Химия,
автор: itzzzzrob
Предмет: Информатика,
автор: liziiii
Предмет: Литература,
автор: StasyXOXO